Beginning Ubuntu Linux - Thomas, Keir; Sicam, Jaime (Apress : Imprint: Apress, 2008)
Beginning Ubuntu Linux, the award-winning and best-selling Ubuntu book for beginners, is now in its third edition, presenting readers with an up-to-the-minute introduction to the world of Linux and the open source community. A detailed overview of Ubuntu's installation and configuration process encourages you to take the plunge and switch to Linux, and from there you'll learn how to wield total control over your newly installed operating system. Guided through the most commonly desired tasks such as printer configuration, listening to audio CDs and MP3s, watching movies, performing office and Internet-related tasks, as well as general system maintenance matters, authors Keir Thomas and Jaime Sicam will soon have you using and enjoying Ubuntu Linux and never looking back. You'll also find a series of comprehensive tutorials on Linux internals and the command-line prompt-essential for any Linux user-along with special sections on optimization, security, and system maintenance that will broaden your knowledge to professional level. The complete Ubuntu Linux distribution is included free on the DVD inside the book. Simply insert the DVD and follow the instructions in the book to install Ubuntu Linux! The ultimate guide to Ubuntu, the hottest Linux distribution on the planet Avoids introductions to esoteric Linux topics that are commonly found in other books and focuses on everyday tasks for everyday users: printer and file sharing configuration, office document management, listening to MP3s, watching movies, and much more Includes a DVD containing not only the complete Ubuntu version, but also versions of Ubuntu's sister projects, including Edubuntu, Kubuntu, and Xubuntu.